Preparation method of Zr-doped Ru-based oxide anode catalyst for efficient and lasting acidic water electrolysis

Preparation of Zr-doped Ru-based oxide catalyst by room temperature stirring, solving the problems of complex preparation process and low activity of existing RuO2 acidic OER electrocatalysts, achieving high efficiency and stability of the catalyst, and demonstrating a good acidic water electrolytic anode catalyst Application potential.

CN119491262AActive Publication Date: 2025-02-21NANKAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411667904.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing RuO2 acidic OER electrocatalyst preparation process is complex, does not have the potential for large-scale application, has low intrinsic activity, is prone to attenuation during operation, and is difficult to be used as anode catalyst in PEM electrolytic cells.

Method used

Preparation of Zr-doped Ru-based oxide catalyst by room temperature stirring, the step includes homogeneous mixing of the Ru metal source with the Zr metal source at room temperature to form a Ru-Zr precursor solution, followed by drying in a vacuum drying chamber and centrifugation washing , and finally calcined in a muffle furnace at high temperature to obtain the Zr-RuO2 catalyst.

Benefits of technology

This method significantly improves the catalytic activity and stability of RuO2-based catalysts, reduces the acidic OER overpotential, extends the stable working time of the catalyst, and demonstrates good application potential of acidic water electrolytic anode catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491262A_ABST
    Figure CN119491262A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a Zr-doped RuO2 acidic water electrolysis anode catalyst, which can be realized only by means of room-temperature stirring and subsequent low-temperature annealing: firstly, sufficiently dissolving a metal precursor under a stirring condition, then evaporating a solvent in a vacuum drying oven, and centrifugally washing solid powder for several times; finally, the dried solid powder is placed in a muffle furnace to be annealed, a crucible is taken out to be naturally cooled, and the Zr-doped RuO2 acidic water electrolysis anode catalyst can be obtained. Compared with an existing preparation method, the preparation method provided by the invention is simple and easy to implement, mild in reaction condition, easy to control, high in repeatability and suitable for large-scale production, and solves the technical problems of high cost, complicated process flow, difficulty in batch synthesis and the like of an electrolytic water catalyst in the prior art; the prepared catalyst shows remarkably enhanced catalytic activity and stability in acidic water electrolysis as an anode material, is superior to self-made RuO2 and commercial RuO2, shows good application potential in large-scale water electrolysis, and has a relatively high industrial research prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts and their preparation, and specifically relates to a Zr-doped RuO catalyst that can be used for efficient and long-lasting acidic water electrolysis. 2 A method for preparing an anode catalyst. Background Art

[0002] Water electrolysis is a promising method for producing hydrogen, which can convert electrical energy driven by sustainable energy into chemical energy stored in hydrogen bonds. Compared with traditional alkaline electrolyzers, proton exchange membrane water electrolyzer (PEMWE) has become a promising green hydrogen production technology due to its lower operating temperature, higher voltage efficiency, higher current density and better compatibility. However, the anodic oxygen evolution reaction (OER) has slow kinetics and usually consumes too much energy, which seriously limits the efficiency of PEMWE. At present, although various catalysts have been developed successively, iridium oxide (IrO 2 ) is still considered as the most advanced anode catalyst because it can withstand highly oxidizing and corrosive conditions. However, its high cost and low mass activity seriously hinder its large-scale application. Recently, ruthenium oxide (RuO 2 ) is considered as an IrO in acidic OER due to its high intrinsic activity and low price. 2 It is known that increasing RuO 2 The initial oxidation state of Ru in the catalyst is optimized to promote the active oxidation of Ru-centered catalysts, which is an effective strategy to improve the electrocatalytic OER performance. For example, Qiao et al. prepared a rutile RuO 2 (Re 0.06 Ru 0.94 O 2 ) electrocatalysts, in which the Re dopant can obtain electrons from the Ru site at the onset potential to activate OER, thereby greatly enhancing the OER activity (Jin, H.; Liu, X.; An, P.; Tang, C.; Yu, H.; Zhang, Q.; Peng, H.; Gu, L.; Zheng, Y.; Song, T.; Davey, K.; Paik, U.; Dong, J.; Qiao, S.;. Nat. Commun.2023, 14, 354.). The Bi-RuO reported by Luo et al. 2 Nanocatalysts can increase Bi by introducing Bi 0.15 Ru 0.85 O 2The initial valence state of Ru in the OER promotes the activation of Ru active sites and promotes the reaction kinetics of acidic OER (Wu, L.; Liang, Q.; Zhao, J.; Zhu, J.; Jia, H.; Zhang, W.; Cai, P.; Luo, W.;. Chinese. J. Catal. 2023, 55, 182-190.). However, during the OER process, the Ru sites are easily over-oxidized at high potentials to form soluble RuO 4 2- species, which usually leads to the collapse of the crystal structure and the dissolution of Ru species, which in turn leads to the formation of RuO 2 Therefore, an effective strategy is developed to balance RuO 2 The relationship between the stability and activity of the base catalyst is crucial for the practical application of PEMWE but is challenging. Summary of the invention

[0003] The purpose of the present invention is to solve the existing RuO 2 Acidic OER electrocatalysts have complex preparation processes, lack of potential for large-scale application, low intrinsic activity, easy attenuation during operation, and are difficult to use as anode catalysts in PEM electrolyzers and other technical issues. This paper provides a general preparation method for Zr-doped Ru-based oxide catalysts, and demonstrates the good application potential of this material as an anode catalyst for acidic water electrolysis.

[0004] Regulating the electronic structure of Ru-based catalysts is a common strategy to improve the activity and stability of catalysts. Metal doping can effectively change the electronic structure of catalysts by changing the coordination environment of active sites, introducing defects, adjusting the Ru valence state to promote Ru active centers, etc., thereby improving the poor stability of Ru-based catalysts and improving the OER activity of catalysts. Experimental results show that Zr doping can significantly reduce the acidic OER overpotential and prolong the RuO 2 Stable working time of the catalyst.

[0005] To achieve the above object, the present invention adopts the following technical solutions: A Zr-doped Ru-based oxide (RuO) for efficient and durable acidic water electrolysis 2 ) A method for preparing an anode catalyst by stirring at room temperature, comprising the following steps: Step 1, dispersing the Ru metal source into deionized water, stirring at room temperature for a period of time to make it evenly mixed, to obtain a Ru precursor solution; Step 2, adding a Zr metal source to the Ru precursor solution synthesized in step 1, maintaining a molar ratio of the Zr metal source to the Ru metal source of 0.05:1-0.2:1, and then stirring at room temperature to obtain a uniform Ru-Zr precursor solution; Step 3, the Ru-Zr precursor solution was placed in a vacuum oven and dried for several hours to obtain a black solid powder; Step 4, washing the obtained black solid powder with deionized water by centrifugation, drying it in a vacuum drying oven, and collecting the solid powder; Step 5: The solid powder obtained in step 4 is placed in a muffle furnace for high temperature calcination, and then naturally cooled to room temperature to obtain a doped Ru-based oxide Zr-RuO 2 .

[0006] Preferably, in step 1, the Ru metal source is RuCl 3 and C 15 H 21 O 6 Ru, stirring time at room temperature is 5-10min.

[0007] Preferably, in step 2, the Zr metal source is ZrCl 4 and Zr(NO 3 ) 4 , the molar ratio of Zr metal source to Ru metal source is 0.05:1-0.2:1, and the stirring time at room temperature is 5-10 min.

[0008] Preferably, in step 3, the vacuum drying temperature is 60-80° C. and the drying time is 4-6 h.

[0009] Preferably, in step 4, deionized water is used for centrifugal washing 4-6 times, with a rotation speed of 8000-13000 rpm and a time of 1-5 min.

[0010] Preferably, in step 4, the vacuum drying temperature is 60-80° C. and the drying time is 2-3 h.

[0011] Preferably, in step 5, the calcination temperature is 270-400° C. and the holding time is 1-3 h.

[0012] Preferably, in steps 1 and 4, the resistivity of the deionized water used is 18.2-18.25 MΩ·cm. Advantages and beneficial effects of the present invention: Compared with the prior art, the method of the present invention uses a wide range of raw materials, requires mild reaction conditions, has high repeatability and is suitable for large-scale production. The present invention provides a Zr-doped RuO with a rutile crystal structure. 2Material Zr-RuO 2 , which showed greatly improved catalytic activity and stability in acidic water electrolysis, outperforming homemade RuO 2 and commercial RuO 2 During stirring at room temperature, RuO 2 Ru 4+ Diffusion from the crystal structure into the solution, Zr in the solution 4+ RuO 2 The introduction of Zr increases the Zr-RuO 2 The initial valence state of Ru in Zr-RuO can be increased, thereby promoting the activation of Ru active sites and improving the reaction kinetics of acidic OER. In addition, the presence of Zr can enhance the electronic interaction to maintain structural stability. Therefore, under acidic conditions, the material exhibits good electrocatalytic OER performance. 2 The PEM electrolyzer with the anode at 250 mA cm -2 The preparation method of the present invention is simple and easy to implement, environmentally friendly, and has the potential for large-scale industrial production. 2 It lays the foundation for the large-scale preparation of based catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The Zr-RuO prepared in Example 1 of the present invention 2 and RuO 2 XRD spectrum of the catalyst; Figure 2 The Zr-RuO prepared in Example 1 of the present invention 2 TEM morphology of the catalyst; Figure 3 The Zr-RuO prepared in Example 1 of the present invention 2 High-resolution XPS spectra of the catalyst; Figure 4 The Zr-RuO prepared in Example 1 of the present invention 2 Catalyst, RuO 2 Catalysts and Commercial RuO 2 Linear sweep voltammetry curve in 0.5 mol / L sulfuric acid solution; Figure 5 The Zr-RuO prepared in Example 1 of the present invention 2 Catalysts and Commercial RuO 2 100 mA cm in 0.5 mol / L sulfuric acid solution -2 Chronopotentiometry curves under current density; Figure 6 The Zr-RuO prepared in Example 1 of the present invention 2 Catalysts and Commercial RuO 2 (a) PEM performance test curve and (b) stability test curve; Figure 7 The Zr prepared in Examples 4, 5 and 15 of the present invention 0.05 -RuO 2 and Zr 0.15 -RuO 2、 Pure RuO 2 Linear sweep voltammetry curve of the sample in 0.5 mol / L sulfuric acid solution. DETAILED DESCRIPTION

[0014] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings and specific implementation methods. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it.

[0015] Zr-doped RuO 2 The preparation method of nanoparticle acidic water electrolysis anode catalyst comprises the following steps: Step 1: At room temperature, RuCl 3 Disperse in deionized water, stir for a period of time at room temperature to mix evenly, and obtain a Ru precursor solution; The metal salt can be dissolved if the stirring time at room temperature is more than 5 min, and 10 min is selected here after optimization. 3 The amount of substance is 0.5-1.0 mmol.

[0016] Step 2: At room temperature, add a certain proportion of ZrCl to the Ru precursor solution synthesized in step 1. 4 , followed by stirring at room temperature to obtain a uniform Ru-Zr precursor solution; The metal salt can be dissolved if the stirring time at room temperature is more than 5 min. Here, 10 min is selected after optimization. The preferred Zr metal source (ZrCl 4 ) is 0.05-0.2 mmol.

[0017] Step 3, placing the Ru-Zr precursor solution in a vacuum drying oven and drying it for several hours to obtain a black solid powder; The drying temperature can be above 60°C. After optimization, 80°C is selected. The drying time needs to be more than 4 hours. After optimization, 6 hours is selected.

[0018] Step 4: Wash the obtained black solid powder by centrifugation with deionized water, dry it in a vacuum drying oven, and collect the solid powder; The deionized water used for centrifugation is 18.25 MΩ·cm, and the preferred number of centrifugal washings is 6 times, the speed is 8000-13000 rpm, and the time is 1-5 min. The purpose is to remove RuO 2 Unstable substances on the surface. Drying temperature can be above 60 ℃. 80 ℃ is selected after optimization. Drying time needs 2-3 hours. 2 hours is selected after optimization.

[0019] Step 5: The solid powder obtained in step 4 is placed in a muffle furnace for high temperature calcination, and then naturally cooled to room temperature to obtain a doped Ru-based oxide Zr-RuO 2 ; The calcination temperature needs to be above 270 °C. 350 °C is selected here after optimization. The insulation time needs to be above 1 h. 2 h is selected here after optimization.

[0020] The reaction conditions involved in the following examples that are not given are the same as those in the above preparation methods and are not repeated here. The raw materials used are analytically pure, conventional chemicals purchased from the market and do not require further treatment. Example

[0021] At room temperature, 1 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 .

[0022] The Zr-doped RuO obtained in Example 1 2 The catalyst was subjected to XRD analysis, and the results were as follows Figure 1 As shown in Figure 2, the oxide crystal structure of the obtained catalyst remains intact, with only the rutile phase RuO 2 The peak of Zr does not form a new phase.

[0023] The Zr-doped RuO obtained in Example 1 2 The nanoparticle water electrolysis anode catalyst was characterized by TEM morphology. Figure 2As shown, the obtained catalyst presents a three-dimensional nanoparticle cross-linked network structure, in which the metal is uniformly dispersed in the form of nanoparticles without agglomeration.

[0024] The Zr-doped RuO obtained in Example 1 2 The Ru 3p spectrum of the catalyst was analyzed by XPS. Figure 3 As shown, the high-resolution XPS spectrum of Ru 3p shows that Ru 3p 3 / 2 and Ru 3p 1 / 2 The peaks are located at 463.2 eV and 484.8 eV, indicating the presence of Ru 4+ With the incorporation of Zr, Zr-RuO 2 MediumRu 3p 3 / 2 and Ru 3p 1 / 2 The peak position of RuO 2 This indicates that with the incorporation of Zr, there is an electronic interaction between Ru and the surrounding atoms. 4+ Acting as an electron donor, the initial oxidation state of Ru is increased, which is beneficial to improve OER activity and promote acidic OER kinetics. In addition, this electronic interaction caused by the dopant has been shown to promote the maintenance of structural stability and improve the electrocatalytic performance by reducing the energy barrier and avoiding excessive oxidation of active species. Therefore, this material is superior to commercial RuO 2 It is expected to further improve the long-term stability of acidic OER.

[0025] The Zr-doped RuO obtained in Example 1 2 Nanoparticle anode catalyst for water electrolysis at 0.5 mol L -1 Linear sweep voltammetry was performed in sulfuric acid solution. Figure 4 As shown, the obtained catalyst outperforms the commercial RuO 2 Acidic OER catalytic activity of the catalysts.

[0026] The Zr-doped RuO obtained in Example 1 2 Nanoparticle anode catalyst for water electrolysis at 0.5 mol L -1 10 mA cm in sulfuric acid solution -2 The chronopotentiometry test was performed at the current density. The results were as follows: Figure 5 As shown, the obtained catalyst outperforms the commercial RuO 2 Long term stability of the catalyst.

[0027] The Zr-doped RuO obtained in Example 1 2 Nanoparticle water electrolysis anode catalyst was used for PEMWE electrolysis test, and the results are as follows Figure 6As shown in (a), Zr-RuO 2 The PEM electrolyzer with the anode at 500 mA cm -2 The voltage at the current density is 1.74 V, which is lower than that of commercial RuO 2 The anode (1.91 V) is 170 mV lower. Figure 6 (b) As shown in Zr-RuO 2 The PEM electrolyzer with the anode at 250 mA cm -2 It can operate stably for more than 140 h at a working current of , with only slight attenuation, reflecting its excellent application potential in industrial water electrolysis. Example

[0028] At room temperature, 0.5 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0029] At room temperature, 0.75 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0030] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.05 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0031] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.15 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0032] At room temperature, 1.0 mmol RuCl 3Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination, the calcination temperature was 270 °C, the heating rate was 5 °C / min, and the insulation time was 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0033] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination, the calcination temperature was 300 °C, the heating rate was 5 °C / min, and the insulation time was 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0034] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4, then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 380 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0035] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination, the calcination temperature was 400 °C, the heating rate was 5 °C / min, and the insulation time was 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0036] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4, then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 1 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0037] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 3 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0038] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4, then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at 350 °C, a heating rate of 10 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0039] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a tube furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0040] At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water and stir for 10 min to fully dissolve it. Then, add 0.1 mmol Zr(NO 3 ) 4, then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0041] At room temperature, 1.0 mmol C 15 H 21 O 6 Ru was added to 40 mL of deionized water and stirred for 10 min to fully dissolve. Subsequently, 0.1 mmol ZrCl 4 , then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1. Example

[0042] At room temperature, 1.0 mmol C 15 H 21 O 6 Ru was added to 40 mL of deionized water and stirred for 10 min to fully dissolve. Subsequently, 0.1 mmol Zr(NO 3 ) 4, then stirred at room temperature for 10 min to obtain a uniform Ru-Zr precursor solution, which was then placed in a vacuum drying oven and dried at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination at a calcination temperature of 350 °C, a heating rate of 5 °C / min, and a holding time of 2 h. After naturally cooling to room temperature, Zr-doped RuO 2 ; The Zr-doped RuO 2 The anode catalyst for water electrolysis was subjected to XRD analysis and TEM morphology characterization analysis, and the results were similar to those in Example 1.

[0043] Comparative Example 1 At room temperature, 1.0 mmol RuCl 3 Add 40 mL of deionized water, stir for 10 min to fully dissolve it, then place it in a vacuum drying oven and dry it at 80 °C for 6 h to obtain a black solid powder. The obtained solid powder was centrifugally washed 6 times with deionized water and placed in a vacuum drying oven, dried at 80 °C for 2 h, and the solid powder was collected; the obtained solid powder was placed in a muffle furnace for high-temperature calcination, the calcination temperature was 350 °C, the heating rate was 5 °C / min, and the holding time was 2 h. After cooling naturally to room temperature, a pure phase Ru-based oxide (RuO 2 ); Comparative Example 1: 2 The catalyst was subjected to XRD analysis, and the results were as follows Figure 1 As shown, the resulting oxide crystal structure exhibits a standard rutile phase RuO 2 The peak.

[0044] Comparative Example 1: 2 The Ru 3p spectrum of the catalyst was analyzed by XPS. Figure 3 As shown in the Ru 3p high-resolution XPS spectrum, Ru 3p 3 / 2 and Ru 3p 1 / 2 The peak position of the peak is similar to that of Zr-RuO 2 The lower binding energy indicates that the incorporation of Zr leads to electronic interactions between Ru and the surrounding atoms.

[0045] The self-made RuO obtained in Comparative Example 1 2 The catalyst was 0.5 mol L -1 Linear sweep voltammetry was performed in sulfuric acid solution. Figure 4 As shown, the catalyst obtained has a -2The overpotential at the current density is close to 300 mV, and the activity is significantly lower than that of Zr-RuO 2 , indicating that Zr doping has an effect on RuO 2 The OER activity of the catalyst is enhanced.

[0046] Since RuCl 3 The changes in the parameters such as the amount of introduction (Examples 2-3), calcination temperature (Examples 6-9), calcination holding time (Examples 10-11), calcination heating rate (Example 12), calcination equipment (Example 13) and metal source (Examples 14-16) did not lead to the preparation of RuO 2 The catalysts show obvious differences in acidic OER electrocatalytic performance, while in RuCl 3 After adding quantitative amount, ZrCl 4 The change of doping amount (Examples 1 and 4-5) resulted in the RuO 2 The acidic OER electrocatalytic performance of the catalysts was significantly different, so the Zr-doped RuO 2 Research and application of water electrolysis anode catalyst as acidic OER electrocatalyst. Figure 4 and Figure 7 As shown, at 10 mA cm -2 At a current density of 2 The acidic OER overpotential of the catalyst is generally between 220 and 270 mV, indicating that although the RuO with different Zr doping amounts 2 The catalytic performance of RuO 2 The catalytic activity of other batches of Zr-RuO prepared by this method is still greatly improved. 2 They still have the potential for application in acidic OER.

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing a Zr-doped Ru-based oxide (RuO2) anode catalyst for efficient and durable acidic water electrolysis, prepared by room temperature stirring method, characterized in that: The method comprises the following preparation steps: Step 1, synthesis of Ru precursor solution: disperse the Ru metal source into deionized water, stir at room temperature to mix evenly, and obtain a Ru precursor solution; Step 2, adding a Zr metal source to the Ru precursor solution synthesized in step 1, and then stirring at room temperature to obtain a uniform Ru-Zr precursor solution; Step 3, drying the Ru-Zr precursor solution in a vacuum drying oven to obtain a black solid powder; Step 4, washing the obtained black solid powder with deionized water by centrifugation, drying it in a vacuum drying oven, and collecting the solid powder; Step 5: calcine the solid powder obtained in step 4 at high temperature in a muffle furnace, and then cool it naturally to room temperature to obtain doped Ru-based oxide Zr-RuO2.

2. The method according to claim 1, characterized in that In step 1, the Ru metal source is RuCl3 and C 15 H 21 O6Ru.

3. The method according to claim 1, characterized in that In step 1, the resistivity of the deionized water used is 18.2-18.25 MΩ·cm. The stirring time at room temperature is 5-10 min.

4. The method according to claim 1, characterized in that: In step 2, the Zr metal source is ZrCl4 and Zr(NO3)4, the molar ratio of the Zr metal source to the Ru metal source is 0.05:1-0.2:1, and the stirring time at room temperature is 5-10 min.

5. The method according to claim 1, characterized in that: In step 3, the vacuum drying temperature is 60-80° C., and the drying time is 4-6 hours.

6. The method according to claim 1, characterized in that In step 4, the number of centrifugal washing is 4-6 times, the rotation speed is 8000-13000 rpm, and the time is 1-5 min; the vacuum drying temperature is 60-80° C., and the drying time is 2-3 h.

7. The method according to claim 1, characterized in that In step 5, the calcination temperature is 270-400° C. and the holding time is 1-3 h.

8. Use of Zr-RuO2 prepared by the method according to any one of claims 1 to 7 as an acidic water electrolysis catalyst.

9. The use according to claim 8, characterized in that: At 10mAcm -2 At a current density of , the overpotential of the Zr-RuO2 in the acidic oxygen evolution reaction (OER) is between 220-300 mV.

10. The use according to claim 8, characterized in that: The proton exchange membrane (PEM) electrolyzer with Zr-RuO2 as anode is at 250 mA cm -2 It can run stably for more than 140 hours at the working current.

Citation Information

Patent Citations

  • Transition metal doped ruthenium oxide nano material, and preparation method and application thereof

    CN115196697A

  • Method for preparing Ru-based oxide catalyst doped with metal atoms on surface by ion exchange method and application of Ru-based oxide catalyst

    CN116288495A

  • Metal-doped ruthenium oxide NANO material, preparation method therefor, and use thereof

    WO2023221315A1